2011
DOI: 10.2308/accr.00000036
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Severity Classifications of Sarbanes-Oxley Section 404 Internal Control Deficiencies

Abstract: We examine detection and severity classification of internal control deficiencies (ICD) identified under Section 404 of the Sarbanes-Oxley Act of 2002. While the cost/benefit balance of auditor testing of internal controls is highly controversial, prior research has not examined auditor versus client detection of ICD, nor has it examined factors auditors consider in judging ICD severity. We find that auditors detect about three-fourths of unremediated ICD, usually though control testing. This finding contrasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
98
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(110 citation statements)
references
References 27 publications
11
98
0
1
Order By: Relevance
“…2 Bedard and Graham (2011) note the ambiguity in the wording choices used to define the categories of internal control deficiencies. A significant deficiency does not require an adverse internal control opinion, yet the guidance provided by the Supreme Court specifically uses the word "significantly" in its language to explain what they consider to be material.…”
Section: Audits Of Internal Control Over Financial Reportingmentioning
confidence: 99%
“…2 Bedard and Graham (2011) note the ambiguity in the wording choices used to define the categories of internal control deficiencies. A significant deficiency does not require an adverse internal control opinion, yet the guidance provided by the Supreme Court specifically uses the word "significantly" in its language to explain what they consider to be material.…”
Section: Audits Of Internal Control Over Financial Reportingmentioning
confidence: 99%
“…In this theme, the papers relate to internal control unit of companies susceptible to audit, regardless of being a private, public, or nonpro t company. e subthemes are as follows: internal control de ciencies, material weaknesses, volunteer management reporting, e ectiveness, human resources, quality, information technology, public reporting, cost, power, reliability, training, transfer of information to the auditor, investment, and e ciency (Bedard & Graham, 2011;Choi, Choi, Hogan, & Lee, 2013;Ettredge, Li, & Sun, 2006;Krishnan, Rama, & Zhang, 2008). It is a new theme not previously described and it emerges with a good representativeness (6%), present in 11-13 years of the research and in 17-21 journals.…”
Section: Emerging Themesmentioning
confidence: 99%
“…Our present study builds on already existing works to provide a wider view of internal controls covering all the elements globally accepted and used like COSO and Basel Committee on Banking Supervision. Bedard and Graham (2011) used the US Sox internal controls which focus on financial reporting. Using internal governance for internal controls, it was found that bank internal governance determined its performance and risk reduction (Dedu & Chitan, 2013).…”
Section: Introductionmentioning
confidence: 99%